Age is not a determinant factor in susceptibility of broilers to H5N2 clade 2.3.4.4 high pathogenicity avian influenza virus. (December 2016) - Bertran, Kateri; Lee, Dong-Hun; Balzli, Charles; Pantin-Jackwood, Mary; Spackman, Erica; Swayne, David
Abstract In 2014–2015, the US experienced an unprecedented outbreak of H5 clade 2.3.4.4 highly pathogenic avian influenza (HPAI) virus. The H5N2 HPAI virus outbreak in the Midwest in 2015 affected commercial turkey and layer farms, but not broiler farms. To assess any potential genetic resistance of broilers and/or age-related effects, we investigated the pathogenesis and transmission of A/turkey/Minnesota/12582/2015 (H5N2) (Tk/MN/15) virus in commercial 5-week-old broilers, 8-week-old broilers, and >30-week-old broiler breeders. The mean bird lethal dose (BLD50 ) was 5.0 log10 mean egg infectious dose (EID50 ) for all age groups. The mean death time (MDT) was statistically not different among the three age groups, ranging between 3.2 and 4.8 days. All broilers that became infected shed high levels of virus with transmission to contacts and demonstrated severe pathology. Mortality and virus shedding results indicated that age is not a determinant factor in susceptibility of broilers to H5N2 clade 2.3.4.4 HPAI virus. Previously, the Tk/MN/15 virus had a BLD50 of 3.6 log10 EID50 and MDT of 2 days in White Leghorn chickens and a BLD50 of 5.0 log10 EID50 and MDT of 5.9 days in turkeys, suggesting that the broiler breed is less susceptible to Midwestern H5N2 virus than the layer breed but similarly susceptible to turkeys. Therefore, genetic resistance of broilers to infection may have accounted only partially for the lack of affected broiler farms in the Midwestern outbreaks, with other contributing factors such as fewer outside to on farm exposure to contacts, type of production management system or enhanced biosecurity.